Preparation method of high corrosion-resistant ultra-high purity stainless steel
Patent Information
- Application Number
- CN202611028355.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-07-10
AI Technical Summary
同时,冶炼过程中生成的非金属夹杂物普遍尺寸粗大、形态棱角化且分布不均,极易成为点蚀优先形核与扩展的源头,导致材料表面钝化膜连续性差、耐蚀稳定性不足
本申请通过三段式梯度精炼耦合高耐蚀成分精准设计,从杂质极限脱除、夹杂物可控改性、成分协同耐蚀三个层面实现突破,与传统工艺相比具备以下显著优点:
Smart Images

Figure CN122521943B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of special alloy smelting technology, and in particular relates to a method for preparing high corrosion-resistant ultra-high purity stainless steel. Background Technology
[0002] 316L stainless steel, containing molybdenum, possesses excellent resistance to pitting corrosion, crevice corrosion, and overall corrosion, making it a core material for harsh corrosive environments such as semiconductors, nuclear power, marine engineering, and high-end chemical equipment. In these high-end applications, the material must simultaneously possess excellent resistance to intergranular corrosion and pitting corrosion, placing extremely high demands on the steel's purity, compositional uniformity, and structural stability.
[0003] Currently, conventional processes such as traditional vacuum induction melting and VD+LF double refining still face significant technical bottlenecks in the preparation of high-end 316L stainless steel. Incomplete deoxidation and desulfurization during conventional smelting processes result in high levels of harmful residues such as oxygen, sulfur, and phosphorus in the steel. This easily induces chromium carbide precipitation and chromium depletion at grain boundaries, significantly increasing the material's susceptibility to intergranular corrosion. Simultaneously, non-metallic inclusions generated during smelting are generally large, angular, and unevenly distributed, readily becoming the primary source of pitting corrosion nucleation and propagation, leading to poor continuity of the passivation film on the material surface and insufficient corrosion resistance.
[0004] Existing technologies mostly employ one-time deoxidation and gradient-free impurity removal designs, without introducing strong electromagnetic stirring to enhance mass transfer or achieving ultra-high vacuum gradient pressure holding refining. This results in a significant upper limit to impurity removal, making it difficult for inclusions to fully float, polymerize, and undergo plastic modification. Although some processes introduce rare earth elements to modify inclusions, they can only control the morphology of already formed inclusions and cannot fundamentally reduce the original oxygen and sulfur content in the molten pool. The improvement in corrosion resistance is limited, and the process window is narrow with poor stability, making it prone to compositional and performance fluctuations in industrial production.
[0005] Furthermore, traditional processes have a relatively crude control over key elements such as carbon, silicon, manganese, and nitrogen, making it difficult to achieve stable and precise matching and synergistic control of ultra-low carbon, high chromium, and molybdenum alloys. This prevents the full integration of advantages in compositional design, high purity, and high corrosion resistance. In summary, existing preparation technologies cannot simultaneously achieve a synergistic improvement in extreme purity, highly precise corrosion-resistant composition, controllable modification of inclusions, and excellent corrosion resistance, thus failing to meet the increasingly stringent service requirements of 316L stainless steel for high-end equipment. Summary of the Invention
[0006] The purpose of this application is to overcome the shortcomings of the existing technology and provide a method for preparing high corrosion-resistant ultra-high purity stainless steel. Through a three-stage coupled refining process of vacuum gradient enhancement, electromagnetic stirring intensity gradient enhancement, and deoxidation-modification functional gradient progression, combined with a high corrosion-resistant composition design of ultra-low carbon, high chromium, molybdenum alloying, and ultra-low harmful impurities, the method achieves the ultimate removal of oxygen, sulfur, and phosphorus, as well as the plasticization, spheroidization, and refinement modification of non-metallic inclusions. This fundamentally inhibits the initiation of intergranular corrosion and pitting corrosion, and significantly improves the corrosion resistance and mechanical properties of stainless steel.
[0007] This application provides a method for preparing high corrosion-resistant ultra-high purity stainless steel, the method comprising: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and clearing to obtain molten steel; the first vacuum degree is ≤5Pa, and the first temperature range is 1520℃-1560℃. Electromagnetic stirring at a first frequency is applied to the molten steel, high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation, and the mixture is kept at a temperature for a first time interval to obtain pre-deoxidized steel liquid; the first frequency is 15Hz-25Hz, the first time interval is 8min-12min, and the oxygen content of the pre-deoxidized steel liquid is ≤50ppm; While maintaining the first vacuum level and the first frequency of electromagnetic stirring, a Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization. The mixture is kept at a temperature for a second time interval to obtain a deep deoxidized molten steel. The mass of the added Mg-Ca composite deoxidizer is 0.03%-0.08% of the mass of the pre-deoxidized molten steel, and the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.5-1:2.5. The second time interval is 10 min-15 min. The vacuum degree of the deep deoxidized molten steel is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, a rare earth modifier is added to the deep deoxidized molten steel for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and the mixture is kept at a temperature for a third time interval to obtain modified molten steel; the second vacuum degree is 0.02Pa-0.05Pa, the second frequency is 30Hz-40Hz, the mass of the rare earth modifier added is 0.01%-0.05% of the mass of the deep deoxidized molten steel, and the third time interval is 5min-8min; The modified molten steel was cast in a protective atmosphere and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The high corrosion-resistant ultra-high purity stainless steel, by mass fraction, is as follows: C≤0.008%, Cr=17.0~17.5%, Ni=14.0~14.5%, Mo=2.5~3.0%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth=0.01~0.05%, with the balance being Fe and unavoidable impurities.
[0008] Optionally, the high-purity raw materials include electrolytic iron with a purity ≥99.95wt%, metallic chromium with a purity ≥99.95wt%, metallic nickel with a purity ≥99.95wt%, ferromolybdenum with a purity ≥99.95wt%, and high-purity carbon powder; the high-purity raw materials are accurately weighed and proportioned according to the target composition after surface cleaning and vacuum drying.
[0009] Optionally, the rare earth modifier is at least one of La, Ce, or La-Ce composite rare earth modifier.
[0010] Optionally, the post-processing includes homogenization annealing, forging, and solution aging.
[0011] Optionally, the high corrosion-resistant ultra-high purity stainless steel product has an oxygen content ≤18ppm, a sulfur content ≤2ppm, a phosphorus content ≤5ppm, and an inclusion fineness rating of D class ≤0.5.
[0012] Optionally, the first vacuum degree is 2Pa-4Pa, and the first frequency is 18Hz-22Hz.
[0013] Optionally, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.8-1:2.2.
[0014] Optionally, the mass of the Mg-Ca composite deoxidizer added is 0.04%-0.06% of the mass of the pre-deoxidized molten steel.
[0015] Optionally, the second vacuum degree is 0.02Pa-0.05Pa, and the second frequency is 33Hz-38Hz.
[0016] Optionally, the mass of the rare earth modifier added is 0.02%-0.04% of the mass of the deep deoxidized molten steel.
[0017] The technical solution provided in this application has the following advantages compared with the prior art: This application achieves breakthroughs in three aspects—limited impurity removal, controllable modification of inclusions, and synergistic corrosion resistance of components—through a three-stage gradient refining process coupled with precise design of highly corrosion-resistant components. Compared with traditional processes, it has the following significant advantages: The vacuum induction furnace is evacuated to a first vacuum level ≤5Pa, which reduces the partial pressure of the gas inside the furnace, thereby reducing the contact opportunities between the high-purity raw materials and gases such as oxygen and nitrogen during the heating process, and reducing the initial content of gaseous impurities in the molten steel. The high-purity raw materials are heated to a first temperature range of 1520℃-1560℃ for molten steel, so that the high-purity raw materials are fully melted to form molten steel, thus laying a stable foundation for subsequent deoxidation, desulfurization, composition homogenization and corrosion resistance improvement.
[0018] Electromagnetic stirring at a first frequency of 15Hz-25Hz is applied to the molten steel, and the electromagnetic force drives the molten steel to generate forced convection, thereby increasing the mass transfer efficiency of each region inside the molten steel and allowing the deoxidizer to fully contact and react with the oxygen in the molten steel. High-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation. The chemical reaction between carbon and oxygen under vacuum conditions generates carbon monoxide gas, which escapes from the vacuum induction furnace under vacuum, thereby initially reducing the oxygen content in the molten steel. The first holding time is 8min-12min, providing sufficient kinetic time for the carbon-oxygen reaction, thereby obtaining a pre-deoxidized steel with an oxygen content ≤50ppm, creating conditions for subsequent deep deoxidation and stable control of corrosion-resistant components.
[0019] Electromagnetic stirring at the first vacuum level and the first frequency is maintained to maintain the vacuum environment and continuously suppress the re-dissolution of gaseous impurities, and electromagnetic stirring is maintained to continuously enhance mass transfer. A Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization. Utilizing the strong affinity of Mg and Ca for oxygen and sulfur, residual oxygen and sulfur in the pre-deoxidized molten steel are further removed, generating MgO-CaO-Al2O3 composite inclusions. The added mass of the Mg-Ca composite deoxidizer is 0.03%-0.08% of the mass of the pre-deoxidized molten steel to ensure sufficient dosage for the deoxidation and desulfurization reaction. The mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.5-1:2.5 to regulate the composition ratio of the composite inclusions, causing the inclusions to transform from a hard, brittle phase to a ductile phase. The second holding time interval is 10-15 minutes to provide sufficient kinetic time for the deep deoxidation and desulfurization reaction, thereby obtaining the deep deoxidized molten steel. By controlling the composition to be ultra-low carbon, low silicon, low manganese, and low nitrogen, grain boundary embrittlement and inclusion-induced localized corrosion are avoided, thereby improving the corrosion resistance uniformity of the steel matrix.
[0020] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree of 0.02Pa-0.05Pa to further reduce the gas partial pressure in the furnace, thereby accelerating the escape of volatile impurities and inhibiting impurity re-dissolution; the frequency of the electromagnetic stirring is increased to a second frequency of 30Hz-40Hz to enhance the electromagnetic stirring intensity, thereby further increasing the convection velocity of the molten pool and accelerating the collision, polymerization and flotation of inclusions; rare earth modifiers are added to the deep deoxidized steel liquid for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, utilizing the reaction between rare earth elements and hard and brittle inclusions to transform residual hard inclusions into ductile rare earth composite inclusions; the mass of the rare earth modifier added is 0.01%-0.05% of the mass of the deep deoxidized steel liquid to ensure the accuracy of the modification reaction dosage; the third holding time interval is 5min-8min to provide sufficient kinetic time for the rare earth modification reaction and the flotation and removal of inclusions, thereby obtaining a modified steel liquid with completely ductile modification of inclusions, eliminating pitting corrosion and localized corrosion nuclei from the root.
[0021] This application simultaneously adopts a high corrosion-resistant composition design: controlling C ≤ 0.008% to suppress chromium depletion at grain boundaries and carbide precipitation, significantly reducing intergranular corrosion sensitivity; controlling Cr = 17.0~17.5%, Ni = 14.0~14.5%, and Mo = 2.5~3.0% to form a stable and dense passivation film, greatly improving resistance to pitting and crevice corrosion; controlling P ≤ 5ppm, S ≤ 2ppm, and O ≤ 18ppm to the limit level, combined with rare earth microalloying of 0.01%~0.05% to purify grain boundaries, achieving a high degree of synergy among composition, purity, and corrosion resistance.
[0022] Finally, the modified molten steel is cast under a protective atmosphere and post-treated to obtain a high-corrosion-resistant, ultra-high-purity stainless steel product. The product achieves oxygen ≤18ppm, sulfur ≤2ppm, phosphorus ≤5ppm, and inclusion fine series D-class rating ≤0.5. It also has excellent high corrosion resistance, with no cracks in intergranular corrosion, low corrosion quality loss, and difficulty in pitting corrosion. Its comprehensive performance is far superior to that of traditional processes. Attached Figure Description
[0023] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.
[0024] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0025] Figure 1 A flowchart illustrating a method for preparing highly corrosion-resistant ultra-high purity stainless steel, provided for embodiments of this application; Figure 2 SEM image of high corrosion-resistant ultra-high purity stainless steel prepared by the preparation method provided in Example 1 of this application; Figure 3 SEM image of stainless steel prepared using the preparation method in Comparative Example 1 of this application. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0027] The range descriptions used herein, such as numerical ranges and proportional ranges, include all possible sub-ranges and single numerical values within the range. For example, a range description of 1 to 6 or 1~6 covers all sub-ranges (such as 1 to 3, 2 to 5, etc.) and single numbers (such as 1, 2, 3, 4, 5, 6) between 1 and 6. Unless otherwise specified, the terms used herein include, but are not limited to, terms such as "include"; relational terms such as "first" and "second" are used only to distinguish different entities or steps and do not imply an actual order or relationship; and / or indicate that multiple situations may exist alone or simultaneously; expressions such as "at least one," "multiple," and "at least one" refer to any combination of the corresponding objects, including combinations of single or multiple objects. Proportional relationships mentioned herein, such as mass ratios and molar ratios, should be understood as the correspondence between the antecedent and consequent terms of a proportional expression, according to the order of description. The raw materials, reagents, instruments, and equipment used herein can all be obtained through commercial purchase or prepared using existing methods.
[0028] Figure 1 A flowchart illustrating a method for preparing high corrosion-resistant ultra-high purity stainless steel, provided in this application embodiment, is shown in the figure: This application provides a method for preparing high corrosion-resistant ultra-high purity stainless steel, the method comprising: S1. High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and clearing to obtain molten steel; the first vacuum degree is ≤5Pa, and the first temperature range is 1520℃-1560℃. S2. Apply electromagnetic stirring at a first frequency to the molten steel, add high-purity carbon powder to the molten steel for vacuum carbon pre-deoxidation, and keep it at a temperature for a first time interval to obtain pre-deoxidized steel liquid; the first frequency is 15Hz-25Hz, the first time interval is 8min-12min, and the oxygen content of the pre-deoxidized steel liquid is ≤50ppm. S3. Maintaining the first vacuum level and the first frequency of electromagnetic stirring, add Mg-Ca composite deoxidizer to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and keep it at the temperature for a second time interval to obtain deep deoxidized molten steel; the added mass of Mg-Ca composite deoxidizer is 0.03%-0.08% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.5-1:2.5, and the second time interval is 10min-15min; S4. Increase the vacuum degree of the deep deoxidized steel liquid to a second vacuum degree, increase the frequency of the electromagnetic stirring to a second frequency, add a rare earth modifier to the deep deoxidized steel liquid for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and hold for a third time interval to obtain modified steel liquid; the second vacuum degree is 0.02Pa-0.05Pa, the second frequency is 30Hz-40Hz, the mass of the rare earth modifier added is 0.01%-0.05% of the mass of the deep deoxidized steel liquid, and the third time interval is 5min-8min; S5. The modified molten steel is cast and molded under a protective atmosphere, and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The high corrosion-resistant ultra-high purity stainless steel, by mass fraction, is as follows: C≤0.008%, Cr=17.0~17.5%, Ni=14.0~14.5%, Mo=2.5~3.0%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth=0.01~0.05%, with the balance being Fe and unavoidable impurities.
[0029] In this embodiment of the application, the "melting and clearing" refers to the state in which the high-purity raw material is completely transformed from a solid to a liquid steel molten state after being heated to the first temperature range.
[0030] Existing technologies employ a one-time deoxidation process with no gradient impurity removal, lacking electromagnetic stirring enhancement and an ultra-high vacuum pressure environment. This results in limitations in impurity removal, residual inclusions, and poor process stability. This application's technical solution constructs a three-stage, gradient-progressive process: vacuum carbon pre-deoxidation → Mg-Ca composite deep deoxidation and desulfurization → ultra-high vacuum electromagnetic stirring coupled with rare earth modification. Through a synergistic mechanism of progressively increasing vacuum level, progressively enhancing electromagnetic stirring frequency, and progressively deepening the function of the deoxidizer, it achieves a dual breakthrough in both the ultimate removal of impurities and the controllable modification of inclusions.
[0031] The first vacuum degree is ≤5Pa, including but not limited to: 1Pa, 2Pa, 3Pa, 4Pa, 5Pa, etc. The first temperature range is 1520℃-1560℃, including but not limited to: 1520℃, 1530℃, 1540℃, 1550℃, 1560℃, etc. The first frequency is 15Hz-25Hz, including but not limited to: 15Hz, 17Hz, 19Hz, 21Hz, 23Hz, 25Hz, etc. The first time range is 8min-12min, including but not limited to: 8min, 9min, 10min, 11min, 12min, etc. The added mass of the Mg-Ca composite deoxidizer is 0.03%-0.08% of the mass of the pre-deoxidized molten steel, including but not limited to: 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, etc. The Mg-Ca composite deoxidizer has a Mg to Ca mass ratio of 1:1.5-1:2.5, including but not limited to: 1:1.5, 1:1.8, 1:2.0, 1:2.2, 1:2.5, etc. The second time interval is 10min-15min, including but not limited to: 10min, 11min, 12min, 13min, 14min, 15min, etc. The second vacuum degree is 0.02Pa-0.05Pa, including but not limited to: 0.02Pa, 0.03Pa, 0.04Pa, 0.05Pa, etc. The second frequency is 30Hz-40Hz, including but not limited to: 30Hz, 32Hz, 34Hz, 36Hz, 38Hz, 40Hz, etc. The rare earth modifier is added at a mass of 0.01%-0.05% of the deep deoxidized molten steel, including but not limited to: 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, etc. The third time interval, 5 min to 8 min, includes, but is not limited to, 5 min, 6 min, 7 min, 8 min, etc.
[0032] In some embodiments, the high-purity raw materials include electrolytic iron with a purity ≥99.95wt%, metallic chromium with a purity ≥99.95wt%, metallic nickel with a purity ≥99.95wt%, ferromolybdenum with a purity ≥99.95wt%, and high-purity carbon powder; the high-purity raw materials are precisely weighed and proportioned according to the target composition after surface cleaning and vacuum drying.
[0033] High-purity raw materials are selected using electrolytic iron (≥99.95wt%), metallic chromium (≥99.95wt%), metallic nickel (≥99.95wt%), ferromolybdenum (≥99.95wt%), and high-purity carbon powder. This reduces the initial content of inherent impurity elements in the high-purity raw materials, thereby reducing the processing load of subsequent deoxidation and desulfurization processes. The high-purity raw materials undergo surface cleaning to remove oxide scale, oil, and adsorbed impurities, thus preventing surface contaminants from entering the molten steel during the melting process. Vacuum drying removes adsorbed moisture, preventing the decomposition of moisture at high temperatures to produce gaseous impurities such as hydrogen and oxygen. Precise weighing and batching according to the target composition ensures that the proportions of each element conform to the design composition of the target steel grade, thus providing a compositional basis for the subsequent preparation of high-corrosion-resistant ultra-high-purity stainless steel products of specific grades.
[0034] The high-purity raw materials with a purity of ≥99.95wt% include, but are not limited to: 99.95wt%, 99.96wt%, 99.97wt%, 99.98wt%, 99.99wt%, etc.
[0035] In some embodiments, the rare earth modifier is at least one of La, Ce, or La-Ce composite rare earth modifiers.
[0036] The rare earth modifier is limited to at least one of La, Ce, or La-Ce composite rare earth modifier. Utilizing the strong affinity of La and Ce for oxygen and sulfur, as well as their reactivity with hard and brittle inclusions, the rare earth modifier ensures effective reaction with residual hard inclusions in deeply deoxidized molten steel. This transforms the hard and brittle inclusions into ductile rare earth composite inclusions, thereby improving the deformability and flotation removal efficiency of the inclusions. By employing the La-Ce composite rare earth modifier, the synergistic effect of La and Ce is utilized to optimize the composition and morphological distribution of the modified inclusions.
[0037] In some embodiments, the post-processing includes homogenization annealing, forging, and solution aging.
[0038] The high-corrosion-resistant ultra-high-purity stainless steel is homogenized by annealing after casting to eliminate component segregation and microstructure inhomogeneity generated during the casting process, thereby making the composition and microstructure of the finished high-corrosion-resistant ultra-high-purity stainless steel product more uniform. The homogenized annealed high-corrosion-resistant ultra-high-purity stainless steel is then forged to give the finished product the required shape and size, thereby meeting the component morphology requirements of specific application scenarios. The forged high-corrosion-resistant ultra-high-purity stainless steel is then solution-aged to control the distribution of precipitates and grain size in the finished product, thereby optimizing the mechanical properties and corrosion resistance of the finished product.
[0039] In some embodiments, the finished high-corrosion-resistant ultra-high-purity stainless steel has an oxygen content ≤18ppm, a sulfur content ≤2ppm, a phosphorus content ≤5ppm, and an inclusion fineness rating of ≤0.5 (Class D). The mass loss after corrosion is ≤100g / cm³. 2 No cracks were found during intergranular corrosion.
[0040] In this embodiment of the application, the inclusion system Class D rating refers to the grade assessment of spherical oxide inclusions according to national standards. The lower the rating value, the less inclusion content and the higher the cleanliness.
[0041] The high corrosion-resistant ultra-high purity stainless steel finished product has an oxygen content ≤18ppm, a sulfur content ≤2ppm, and a phosphorus content ≤5ppm, thus breaking through the bottleneck of impurity removal in existing technologies where the oxygen content is ≥30ppm and the sulfur content is ≥5ppm; it also achieves an inclusion fineness D-class rating ≤0.5, thus breaking through the inclusion control bottleneck of inclusion fineness D-class rating 1.5-2.5 in existing technologies; and the mass loss after corrosion is ≤100g / cm³. 2 The absence of cracks during intergranular corrosion overcomes the bottleneck of corrosion resistance in traditionally smelted stainless steel, which suffers from high susceptibility to intergranular corrosion and frequent pitting failure. Achieving these performance indicators is achieved in two ways: firstly, the ultra-low content of harmful impurities effectively inhibits chromium depletion at grain boundaries and carbide precipitation along grain boundaries, significantly reducing the probability of intergranular corrosion initiation; secondly, the refinement and spheroidization modification of inclusions eliminates preferential corrosion nucleation sites, preventing brittle inclusions from cracking under stress. This fundamentally eliminates the stress concentration and corrosion cracking risks induced by hard, brittle inclusions, thus meeting the stringent service requirements of high corrosion-resistant ultra-high purity stainless steel in the semiconductor, nuclear power, and aerospace industries.
[0042] The oxygen content is ≤18ppm, including but not limited to: 10ppm, 11ppm, 12ppm, 13ppm, 14ppm, 15ppm, etc. The sulfur content is ≤2ppm, including but not limited to: 0.5ppm, 1ppm, 1.5ppm, 2ppm, etc. The phosphorus content is ≤5ppm, including but not limited to: 2ppm, 3ppm, 4ppm, 5ppm, etc. The inclusion fineness is rated D grade ≤0.5, including but not limited to: grade 0, 0.5, etc. The mass loss after corrosion is ≤100g / cm³. 2 including but not limited to 30g / cm 2 50g / cm 2 70g / cm 2 90g / cm 2 wait.
[0043] In some embodiments, the first vacuum level is 2Pa-4Pa, and the first frequency is 18Hz-22Hz.
[0044] The first vacuum degree is limited to 2Pa-4Pa, and further narrowed within the range of ≤5Pa, thereby ensuring a sufficiently low residual gas partial pressure during the melting and cleaning stage. The sufficiently low residual gas partial pressure suppresses the secondary adsorption of oxygen and nitrogen during the melting of high-purity raw materials, thus providing better initial conditions for achieving an oxygen content of ≤50ppm in the pre-deoxidized steel liquid. At the same time, it avoids excessive increases in equipment costs and operational complexity caused by excessively low vacuum, thereby achieving a balance between impurity removal efficiency and industrial economics.
[0045] The first frequency is limited to 18Hz-22Hz, and further narrowed within the range of 15Hz-25Hz to optimize the electromagnetic stirring intensity of the molten steel during the pre-deoxidation stage. Optimizing the electromagnetic stirring intensity allows for sufficient contact and reaction between carbon powder and oxygen in the molten steel, thereby improving the kinetic efficiency of vacuum carbon pre-deoxidation. This application is equipped with a high corrosion-resistant composition design: controlling C ≤ 0.008% to suppress chromium depletion at grain boundaries and carbide precipitation, reducing the tendency for intergranular corrosion; a Cr=17.0~17.5%, Ni=14.0~14.5%, Mo=2.5~3.0% ratio to construct a dense passivation film, enhancing resistance to pitting and crevice corrosion; relying on the vacuum deoxidation process of this stage to strictly control the upper limits of O, S, and P impurities, followed by rare earth micro-alloying to purify grain boundaries, achieving a synergistic improvement in composition, purity, and corrosion resistance; moderate stirring parameters can also prevent molten pool splashing and high energy consumption, balancing mass transfer efficiency and production stability, and avoiding excessive energy consumption.
[0046] The first vacuum level is 2Pa-4Pa, including but not limited to: 2Pa, 2.5Pa, 3Pa, 3.5Pa, 4Pa, etc. The first frequency is 18Hz-22Hz, including but not limited to: 18Hz, 19Hz, 20Hz, 21Hz, 22Hz, etc.
[0047] In some embodiments, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.8-1:2.2.
[0048] The mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is limited to 1:1.8-1:2.2, and further narrowed within the range of 1:1.5-1:2.5, thereby optimizing the synergistic ratio of Mg and Ca in the composite deoxidizer. The optimized synergistic ratio makes the composition ratio of MgO-CaO-Al2O3 composite inclusions in the deoxidation product tend to be optimal, thereby promoting the transformation of inclusions from hard and brittle phases to plastic phases. At the same time, it avoids volatilization loss caused by excessive Mg ratio or excessive local reaction caused by excessive Ca ratio, thus achieving a balance between deoxidation efficiency and inclusion modification quality.
[0049] The mass ratio of Mg to Ca is 1:1.8 to 1:2.2, including but not limited to: 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, etc.
[0050] In some embodiments, the mass of the Mg-Ca composite deoxidizer added is 0.04%-0.06% of the mass of the pre-deoxidized molten steel.
[0051] The addition mass of the Mg-Ca composite deoxidizer is limited to 0.04%-0.06% of the mass of the pre-deoxidized molten steel, and further narrowed within the range of 0.03%-0.08% to ensure sufficient reducing agent dosage for the deep deoxidation and desulfurization reaction. Sufficient reducing agent dosage ensures that residual oxygen and sulfur in the pre-deoxidized molten steel are fully removed, thereby improving the purity of the deep deoxidized molten steel. At the same time, it avoids the waste of auxiliary materials and excessive formation of inclusions caused by excessive addition, thus achieving a balance between deimpurity efficiency and auxiliary material economy.
[0052] The added mass of the Mg-Ca composite deoxidizer is 0.04%-0.06% of the mass of the pre-deoxidized molten steel, including but not limited to: 0.04%, 0.045%, 0.05%, 0.055%, 0.06%, etc.
[0053] In some embodiments, the second vacuum degree is 0.02 Pa to 0.05 Pa, and the second frequency is 33 Hz to 38 Hz.
[0054] The second vacuum degree is limited to 0.02Pa-0.05Pa, and further narrowed within this range to ensure extremely low residual gas partial pressure during the rare earth modification stage. This extremely low residual gas partial pressure accelerates the final escape of volatile impurities and completely suppresses the re-dissolution of impurities in the deep deoxidized steel during the modification process, thus providing the final vacuum guarantee for achieving oxygen content ≤18ppm and sulfur content ≤2ppm in the modified steel. At the same time, it avoids the extreme operation of equipment and the surge in costs caused by excessively low vacuum, thereby achieving a balance between extreme depurification and industrial feasibility.
[0055] The second frequency is limited to 33Hz-38Hz, and further narrowed within the range of 30Hz-40Hz, thereby optimizing the electromagnetic stirring intensity of the deep deoxidized steel melt during the rare earth modification stage. The optimized electromagnetic stirring intensity allows the residual hard inclusions to fully collide and contact with the rare earth modifier, thereby accelerating the transformation of the inclusions into plastic rare earth composite inclusions. At the same time, the enhanced stirring convection accelerates the polymerization and flotation of the modified inclusions, thereby improving the removal efficiency of the inclusions. Meanwhile, it avoids excessive turbulence in the molten pool and uneven distribution of rare earth elements caused by excessive stirring frequency, thus achieving a balance between modification efficiency and compositional uniformity.
[0056] The second frequency is 33Hz-38Hz, including but not limited to: 33Hz, 34Hz, 35Hz, 36Hz, 37Hz, 38Hz, etc. The second vacuum degree is 0.02Pa-0.05Pa, including but not limited to: 0.02Pa, 0.025Pa, 0.03Pa, 0.04Pa, 0.045Pa, etc.
[0057] In some embodiments, the mass of the rare earth modifier added is 0.02%-0.04% of the mass of the deep deoxidized molten steel.
[0058] The addition of the rare earth modifier is limited to 0.02%-0.04% of the mass of the deep deoxidized steel liquid, and further narrowed within the range of 0.01%-0.05% to ensure sufficient modifier dosage for the rare earth modification reaction. Sufficient modifier dosage allows the residual hard inclusions in the deep deoxidized steel liquid to be completely converted into ductile rare earth composite inclusions, thereby achieving the goal of inclusion fine series D-class rating ≤0.5. At the same time, it avoids rare earth enrichment segregation and the formation of new impurity phases caused by excessive addition, thus achieving a balance between complete modification and process stability.
[0059] The rare earth modifier is added at a mass of 0.02%-0.04% of the mass of the deep deoxidized molten steel, including but not limited to: 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, etc.
[0060] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. Experimental methods in the following embodiments that do not specify specific conditions are generally determined according to industry standards. If there is no corresponding industry standard, then generally accepted international standards, conventional conditions, or conditions recommended by the manufacturer are followed.
[0061] Example 1: High corrosion resistance, ultra-high purity 316L stainless steel Ingredients: 99.96% pure electrolytic iron, 99.98% pure metallic chromium, 99.97% pure metallic nickel, 99.95% pure metallic molybdenum, and high-purity carbon powder; the high-purity raw materials are precisely weighed and formulated according to the target composition after surface cleaning and vacuum drying, with the following composition: C≤0.008%, Cr: 17.2%, Ni: 14.3%, Mo: 2.8%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth 0.03%, and the balance being Fe and unavoidable impurities.
[0062] Process steps: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel; the first vacuum degree is 3 Pa, and the first temperature range is 1540℃.
[0063] Electromagnetic stirring at a first frequency is applied to the molten steel, and high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation. The mixture is kept at a temperature for a first time interval to obtain a pre-deoxidized steel liquid. The first frequency is 20 Hz, the first time interval is 10 min, and the oxygen content of the pre-deoxidized steel liquid is 32 ppm.
[0064] While maintaining the first vacuum level and the first frequency of electromagnetic stirring, Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and the mixture is kept at a temperature for a second time interval to obtain deep deoxidized molten steel; the added mass of Mg-Ca composite deoxidizer is 0.05% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:2, and the second time interval is 12 min.
[0065] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, a rare earth modifier is added to the deep deoxidized steel liquid for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and the liquid is kept at a temperature for a third time interval to obtain modified steel liquid; the second vacuum degree is 0.04 Pa, the second frequency is 35 Hz, the rare earth modifier is La, the added mass of the rare earth modifier is 0.03% of the mass of the deep deoxidized steel liquid, and the third time interval is 6 min.
[0066] The modified molten steel is cast under a protective atmosphere and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The post-treatment includes homogenization annealing, forging, and solution treatment. The homogenization annealing temperature is 1200℃, and the solution treatment temperature is 1060℃.
[0067] Test results: O=16ppm, S=2ppm, P=4ppm, inclusions Class D, Grade 0, Rm=595MPa, A=75%. Mass loss after corrosion: 52g / cm³. 2 No cracks were found during intergranular corrosion.
[0068] Example 2: High corrosion resistance, ultra-high purity 316L stainless steel Ingredients: 99.95% pure electrolytic iron, 99.97% pure metallic chromium, 99.96% pure metallic nickel, 99.95% pure metallic molybdenum, and high-purity carbon powder; the high-purity raw materials are precisely weighed and proportioned according to the target composition after surface cleaning and vacuum drying, with the following composition: C≤0.008%, Cr: 17.2%, Ni: 14.7%, Mo: 2.6%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth 0.02%, and the balance being Fe and unavoidable impurities.
[0069] Process steps: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel; the first vacuum degree is 2 Pa, and the first temperature range is 1520℃.
[0070] Electromagnetic stirring at a first frequency is applied to the molten steel, and high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation. The mixture is kept at a temperature for a first time interval to obtain a pre-deoxidized steel liquid. The first frequency is 18 Hz, the first time interval is 12 min, and the oxygen content of the pre-deoxidized steel liquid is 38 ppm.
[0071] While maintaining the first vacuum level and the first frequency of electromagnetic stirring, Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and the mixture is kept at a temperature for a second time interval to obtain deep deoxidized molten steel; the added mass of Mg-Ca composite deoxidizer is 0.03% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.5, and the second time interval is 15 min.
[0072] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, a rare earth modifier is added to the deep deoxidized steel liquid for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and the liquid is kept at a temperature for a third time interval to obtain modified steel liquid; the second vacuum degree is 0.02 Pa, the second frequency is 30 Hz, the rare earth modifier is La, the added mass of the rare earth modifier is 0.01% of the mass of the deep deoxidized steel liquid, and the third time interval is 8 min.
[0073] The modified molten steel is cast under a protective atmosphere and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The post-treatment includes homogenization annealing, forging, and solution treatment. The homogenization annealing temperature is 1200℃, and the solution treatment temperature is 1060℃.
[0074] Test results: O=9ppm, S=2ppm, P=5ppm, inclusions Class D, Grade 0, Rm=590MPa, A=74%. Mass loss after corrosion: 32g / cm³. 2 No cracks were found during intergranular corrosion.
[0075] Example 3: High corrosion-resistant ultra-high purity 316L stainless steel Ingredients: 99.97% pure electrolytic iron, 99.98% pure metallic chromium, 99.97% pure metallic nickel, 99.96% pure metallic molybdenum, and high-purity carbon powder; the high-purity raw materials are precisely weighed and formulated according to the target composition after surface cleaning and vacuum drying, with the following composition: C≤0.008%, Cr 17.5%, Ni 14.0%, Mo 3.0%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth 0.04%, and the balance being Fe and unavoidable impurities.
[0076] Process steps: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel; the first vacuum degree is 4 Pa, and the first temperature range is 1560℃.
[0077] Electromagnetic stirring at a first frequency is applied to the molten steel, and high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation. The mixture is kept at a temperature for a first time interval to obtain a pre-deoxidized steel liquid. The first frequency is 22 Hz, the first time interval is 8 min, and the oxygen content of the pre-deoxidized steel liquid is 45 ppm.
[0078] While maintaining the first vacuum level and the first frequency of electromagnetic stirring, Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and the mixture is kept at a temperature for a second time interval to obtain deep deoxidized molten steel; the added mass of Mg-Ca composite deoxidizer is 0.06% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:2.2, and the second time interval is 10 min.
[0079] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, a rare earth modifier is added to the deep deoxidized steel liquid for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and the liquid is kept at a temperature for a third time interval to obtain modified steel liquid; the second vacuum degree is 0.05 Pa, the second frequency is 38 Hz, the rare earth modifier is Ce, the added mass of the rare earth modifier is 0.04% of the mass of the deep deoxidized steel liquid, and the third time interval is 5 min.
[0080] The modified molten steel is cast under a protective atmosphere and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The post-treatment includes homogenization annealing, forging, and solution treatment. The homogenization annealing temperature is 1200℃, and the solution treatment temperature is 1060℃.
[0081] Test results: O=18ppm, S=1ppm, P=3ppm, inclusions Class D, grade 0.5, Rm=585MPa, A=73%. Mass loss after corrosion: 58g / cm³. 2 No cracks were found during intergranular corrosion.
[0082] Comparative Example 1: Traditional single aluminum deoxidation (without high corrosion-resistant components in the design) The conventional VIM+VD process was used, with single aluminum deoxidation, no multi-field coupling and rare earth modification, and the high corrosion-resistant composition design (Cr=16.0%, Ni=12.0%, Mo=2.0%, C=0.03%) described in this application was not adopted.
[0083] Test results: O=45ppm, S=8ppm, P=7ppm, inclusions Class D, Grade 2.0, Rm=480MPa, A=52%. Mass loss after corrosion: 158g / cm³. 2 No cracks were found during intergranular corrosion.
[0084] Comparative Example 2: Traditional VD+LF dual refining (without high corrosion-resistant components) The process employs conventional industrial VD+LF technology, Si-Ca deoxidation, weak argon stirring, no rare earth treatment, and does not use the high corrosion-resistant composition design described in this application (Cr=16.5%, Ni=13.0%, Mo=2.2%, C=0.025%).
[0085] Test results: O=69ppm, S=10ppm, P=8ppm, inclusions Class D, Grade 2.5, Rm=460MPa, A=49%. Mass loss after corrosion: 206g / cm³. 2 Intergranular corrosion can cause cracks.
[0086] Comparative Example 3: No electromagnetic stirring (with component design) Ingredients: Electrolytic iron with a purity ≥99.95wt%, metallic chromium with a purity ≥99.95wt%, metallic nickel with a purity ≥99.95wt%, ferromolybdenum with a purity ≥99.95wt%, and high-purity carbon powder; the high-purity raw materials are precisely weighed and formulated according to the target composition after surface cleaning and vacuum drying, with the following composition: C≤0.008%, Cr 17.2%, Ni 14.3%, Mo 2.8%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, rare earth 0.03%, and the balance being Fe and unavoidable impurities.
[0087] Process steps: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel; the first vacuum degree is 3 Pa, and the first temperature range is 1540℃.
[0088] High-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation, and the mixture is kept at a constant temperature for a first time interval to obtain pre-deoxidized steel liquid; the first time interval is 10 min, and the oxygen content of the pre-deoxidized steel liquid is 42 ppm.
[0089] A Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and the mixture is kept at a temperature for a second time interval to obtain a deep deoxidized molten steel. The mass of the Mg-Ca composite deoxidizer added is 0.05% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:2, and the second time interval is 12 min.
[0090] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree, and a rare earth modifier is added to the deep deoxidized steel liquid for ultra-high vacuum rare earth modification. The liquid is then kept at a temperature for a third time interval to obtain modified steel liquid. The second vacuum degree is 0.05 Pa, the rare earth modifier is La, the added mass of the rare earth modifier is 0.03% of the mass of the deep deoxidized steel liquid, and the third time interval is 6 min.
[0091] The modified molten steel is cast into shape under a protective atmosphere and then post-treated to obtain stainless steel finished products. The post-treatment includes homogenization annealing, forging and solution treatment. The homogenization annealing temperature is 1200℃ and the solution treatment temperature is 1060℃.
[0092] Test results: O=35ppm, S=5ppm, P=6ppm, inclusions Class D, Grade 1.5, Rm=500MPa, A=60%. Mass loss after corrosion: 118g / cm³. 2 No cracks were found during intergranular corrosion.
[0093] Comparative Example 4: No rare earth modification (with composition design) Ingredients: Electrolytic iron with a purity ≥99.95wt%, metallic chromium with a purity ≥99.95wt%, metallic nickel with a purity ≥99.95wt%, ferromolybdenum with a purity ≥99.95wt%, and high-purity carbon powder; the high-purity raw materials are precisely weighed and batched according to the target composition after surface cleaning and vacuum drying, with the following composition: C≤0.008%, Cr17.2%, Ni14.3%, Mo2.8%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.005%, S≤0.0002%, O≤0.0018%, and the balance being Fe and unavoidable impurities.
[0094] Process steps: High-purity raw materials are loaded into a vacuum induction furnace, the vacuum induction furnace is evacuated to a first vacuum degree, and the high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel; the first vacuum degree is 4 Pa, and the first temperature range is 1530℃.
[0095] Electromagnetic stirring at a first frequency is applied to the molten steel, and high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation. The mixture is kept at a temperature for a first time interval to obtain a pre-deoxidized steel liquid. The first frequency is 18 Hz, the first time interval is 11 min, and the oxygen content of the pre-deoxidized steel liquid is 39 ppm.
[0096] While maintaining the first vacuum level and the first frequency of electromagnetic stirring, Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel for composite deep deoxidation and desulfurization, and the mixture is kept at a temperature for a second time interval to obtain deep deoxidized molten steel; the added mass of Mg-Ca composite deoxidizer is 0.04% of the mass of the pre-deoxidized molten steel, the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:2.2, and the second time interval is 13 min.
[0097] The vacuum degree of the deep deoxidized steel liquid is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, and the liquid is kept at a temperature for a third time interval to obtain modified steel liquid; the second vacuum degree is 0.05 Pa, the second frequency is 33 Hz, and the third time interval is 7 min.
[0098] The modified molten steel is cast into shape under a protective atmosphere and then post-treated to obtain stainless steel finished products. The post-treatment includes homogenization annealing, forging and solution treatment. The homogenization annealing temperature is 1180℃ and the solution treatment temperature is 1050℃.
[0099] Test results: O=28ppm, S=4ppm, P=5ppm, inclusions Class D, Grade 1.0, Rm=540MPa, A=68%. Mass loss after corrosion: 116g / cm³. 2 No cracks were found during intergranular corrosion.
[0100] Experimental methods for evaluating results: Oxygen content determination method: The inert gas melting-infrared absorption method is adopted. High corrosion-resistant ultra-high purity stainless steel finished products or molten steel samples are melted in an inert atmosphere. The released oxygen reacts with carbon monoxide to generate carbon dioxide, and the oxygen content is quantitatively determined by an infrared detector.
[0101] Sulfur content determination method: The high-frequency combustion-infrared absorption method is used. High corrosion-resistant ultra-high purity stainless steel finished products or molten steel samples are burned in a high-frequency induction furnace, and the sulfur oxides released are quantitatively determined by infrared detector.
[0102] Phosphorus content determination method: Inductively coupled plasma atomic emission spectrometry (ICP-AES) is used. After the high corrosion-resistant ultra-high purity stainless steel finished product or molten steel sample is dissolved in acid, the phosphorus content is quantitatively determined by ICP-AES.
[0103] Method for determining the Class D rating of inclusions: According to GB / T 10561-2005 "Determination of Non-metallic Inclusion Content in Steel - Standard Rating Chart Microscopic Examination Method", metallographic samples of high corrosion-resistant ultra-high purity stainless steel products are prepared, and the spherical oxide inclusions are rated as Class D under an optical microscope using the standard rating chart comparison method.
[0104] Method for determining tensile strength Rm: According to GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test at room temperature", high corrosion-resistant ultra-high purity stainless steel finished products are processed into standard tensile specimens, stretched at a specified rate on a universal testing machine, the maximum force is recorded and the tensile strength Rm is calculated.
[0105] Method for determining elongation at fracture A: According to GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test at room temperature", high corrosion-resistant ultra-high purity stainless steel finished products are processed into standard tensile specimens, stretched at a specified rate on a universal testing machine until fracture, the gauge length after fracture is measured and the elongation at fracture A is calculated.
[0106] Method for determining mass loss after corrosion: According to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", high corrosion resistant ultra-high purity stainless steel finished products are processed into standard corrosion samples and subjected to neutral salt spray test (NSS) in a salt spray test chamber. The test cycle is 720h. After the test, the samples are cleaned and the mass loss per unit area is calculated.
[0107] Intergranular corrosion test method: According to Method E (sulfuric acid-copper sulfate corrosion test) in GB / T 4334-2020 "Corrosion of metals and alloys - Test method for intergranular corrosion of austenitic and ferritic-austenitic (duplex) stainless steel", high corrosion resistant ultra-high purity stainless steel products are processed into standard intergranular corrosion samples. After sensitization treatment, corrosion test is carried out. The presence of intergranular corrosion cracks in the bent parts of the sample is observed by metallographic microscope.
[0108] Table 1: Comparison of Effect Data between Examples and Comparative Examples As can be seen from the examples and comparative data, the technical advancements of this application include: 1. Limit removal of harmful impurities The examples show oxygen content ≤18ppm, sulfur content ≤2ppm, and phosphorus content ≤5ppm, all meeting ultra-high purity standards. Comparative Example 1 shows oxygen content of 45ppm and sulfur content of 8ppm; Comparative Example 2 shows oxygen content of 52ppm and sulfur content of 10ppm; Comparative Example 3 shows oxygen content of 35ppm and sulfur content of 5ppm; and Comparative Example 4 shows oxygen content of 28ppm and sulfur content of 4ppm. Compared to existing technologies, this application reduces oxygen content by more than 60% and sulfur content by more than 75%.
[0109] 2. Significantly improved accuracy in controlling inclusions. The inclusions in the embodiments are rated as Class D ≤ 0.5, while Comparative Example 1 is rated as 2.0, Comparative Example 2 as 2.5, Comparative Example 3 as 1.5, and Comparative Example 4 as 1.0. The inclusion control level of this application is 1-2 orders of magnitude higher than that of the prior art.
[0110] 3. Significantly improved mechanical properties The tensile strength Rm of the example is ≥585MPa and the elongation after fracture A is ≥73%; the tensile strength of Comparative Example 1 is 480MPa and the elongation after fracture is 52%, and the tensile strength of Comparative Example 2 is 460MPa and the elongation after fracture is 49%. The tensile strength of this application is increased by more than 20%, and the plasticity is increased by more than 40%.
[0111] 4. Verification of high corrosion-resistant component design and multi-field coupling synergistic effect Comparative Examples 1 and 2 did not adopt the high corrosion-resistant composition design of this application (low Cr, Ni, and Mo content, high C content), and the mass loss after corrosion was as high as 158-206 g / cm³. 2 Furthermore, intergranular corrosion cracks appeared in Comparative Example 2, proving the fundamental role of composition design in ensuring corrosion resistance.
[0112] Comparative Example 3 (with compositional design but without electromagnetic stirring) had an oxygen content of 35 ppm and inclusion class D 1.5, while Comparative Example 4 (with compositional design but without rare earth modification) had an oxygen content of 28 ppm and inclusion class D 1.0, both significantly inferior to the examples. This demonstrates that, based on the same high corrosion-resistant compositional design, the synergistic effect of ultra-high vacuum electromagnetic stirring coupled with rare earth modification is key to achieving extreme deimpurification and precise inclusion control.
[0113] Example: Mass loss after corrosion ≤ 58 g / cm³ 2 Compared with Comparative Example 1, the corrosion rate was reduced by more than 67%, and compared with Comparative Example 3 and Comparative Example 4 (which had composition design but lacked field coupling) by more than 50%, and all of them were free of intergranular corrosion cracks, which fully demonstrates the synergistic effect of the three-stage gradient progressive process and the high corrosion-resistant composition design of this application.
[0114] Detailed explanation of the attached diagram: Figure 2 Scanning electron micrograph (×6000) of the ultra-high purity 316L stainless steel in Example 1 of this application. It can be clearly seen from the figure that the steel matrix has high cleanliness, with very few inclusions that are diffusely distributed, and no large-sized hard and brittle inclusions are observed. The purity of the matrix is significantly better than that of traditional processes.
[0115] Figure 3 Scanning electron micrograph (×500) of the stainless steel obtained by the conventional single aluminum deoxidation process in Comparative Example 1 of this application. It can be clearly seen from the figure that there are many large blocky and irregular inclusions in the steel matrix. The inclusions are relatively concentrated, and the purity of the matrix is significantly different from that of Example 1.
[0116] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing highly corrosion-resistant ultra-high purity stainless steel, characterized in that, The method includes: High-purity raw materials are loaded into a vacuum induction furnace, which is then evacuated to a first vacuum level. The high-purity raw materials are heated to a first temperature range for melting and cleaning to obtain molten steel. The first vacuum level is 2 Pa-4 Pa, and the first temperature range is 1520℃-1560℃. The high-purity raw materials include electrolytic iron with a purity ≥99.95wt%, metallic chromium with a purity ≥99.95wt%, metallic nickel with a purity ≥99.95wt%, metallic molybdenum with a purity ≥99.95wt%, and high-purity carbon powder. After surface cleaning and vacuum drying, the high-purity raw materials are precisely weighed and proportioned according to the target composition. Electromagnetic stirring at a first frequency is applied to the molten steel, high-purity carbon powder is added to the molten steel for vacuum carbon pre-deoxidation, and the mixture is kept at a temperature for a first time interval to obtain pre-deoxidized steel liquid; the first frequency is 15Hz-25Hz, the first time interval is 8min-12min, and the oxygen content of the pre-deoxidized steel liquid is ≤50ppm; While maintaining the first vacuum level and the first frequency of electromagnetic stirring, a Mg-Ca composite deoxidizer is added to the pre-deoxidized molten steel to perform composite deep deoxidation and desulfurization to generate MgO-CaO-Al2O3 composite inclusions. The mixture is kept at a temperature for a second time interval to obtain a deep deoxidized molten steel. The mass of the added Mg-Ca composite deoxidizer is 0.03%-0.08% of the mass of the pre-deoxidized molten steel, and the mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.5-1:2.
5. The second time interval is 10 min-15 min. The vacuum degree of the deep deoxidized molten steel is increased to a second vacuum degree, the frequency of the electromagnetic stirring is increased to a second frequency, a rare earth modifier is added to the deep deoxidized molten steel for ultra-high vacuum electromagnetic stirring coupled with rare earth modification, and the mixture is kept at a temperature for a third time interval to obtain modified molten steel; the second vacuum degree is 0.02Pa-0.05Pa, the second frequency is 30Hz-40Hz, the mass of the rare earth modifier added is 0.01%-0.05% of the mass of the deep deoxidized molten steel, and the third time interval is 5min-8min; The modified molten steel was cast in a protective atmosphere and then post-treated to obtain a high corrosion-resistant ultra-high purity stainless steel product. The high corrosion-resistant ultra-high purity stainless steel, by mass fraction, is as follows: C≤0.008%, Cr=17.0~17.5%, Ni=14.0~14.5%, Mo=2.5~3.0%, Si≤0.10%, Mn≤0.50%, N≤0.010%, P≤0.0005%, S≤0.0002%, O≤0.0018%, rare earth=0.01~0.05%, with the balance being Fe and unavoidable impurities.
2. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The rare earth modifier is at least one of La, Ce, or La-Ce composite rare earth modifier.
3. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The post-treatment includes homogenization annealing, forging, and solution treatment to stabilize the microstructure and improve corrosion resistance.
4. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The first frequency is 18Hz-22Hz.
5. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The mass ratio of Mg to Ca in the Mg-Ca composite deoxidizer is 1:1.8-1:2.
2.
6. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The mass of the Mg-Ca composite deoxidizer added is 0.04%-0.06% of the mass of the pre-deoxidized molten steel.
7. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The second frequency is 33Hz-38Hz.
8. The method for preparing high corrosion-resistant ultra-high purity stainless steel according to claim 1, characterized in that, The mass of the rare earth modifier added is 0.02%-0.04% of the mass of the deep deoxidized molten steel.
Citation Information
Patent Citations
Stainless steel welding material smelting desulfurization method
CN112626313A
Ultrahigh-purity 316L stainless steel and preparation method thereof
CN117987747A
Method for preparing ultra-pure stainless steel
CN122256797A